Overview Of The Behavior Of Caring Clinical Perceptor Towards Nurse Professional Students At Gorontalo State University - Dewi Suryaningsi Hiola (International Journal of Education, Vocational and Social Science, 2025)
Caring is the core of nursing practice which is considered an important indicator in carrying out nursing care which is included in one of the assessments for health service users of the nursing profession. Clinical preceptors play the role of nurse teachers who have an important role and a great contribution in helping and supporting students during the process of clinical learning activities, in order to achieve clinical learning competencies and goals. The purpose of this study is to find out the description of the behavior of caring clinical preceptors for nursing professional students at Gorontalo State University. The design in this study uses a descriptive research design. The population in this study is all UNG regular nurse professional students batch XI and XII who are pursuing professional nursing education at UNG which totals 113 respondents. The research sample amounted to 112 respondents with a total sampling technique. The research instrument used a questionnaire. The results of this study showed that as many as 74 respondents (66.1%) rated the caring behavior of clinical preceptors as good and as many as 38 respondents (33.9%) assessed the caring behavior of clinical preceptors as adequate. In conclusion, most of the respondents were nurse professional students who rated their clinic's caring behavior as in the good category. Suggestions for clinical prescribers can further improve the application of caring behavior in guiding nursing professional students who are practicing in a hospital institution.